Interpretação e linguagem em Donald Davidson - Tatiana Maciel Gontijo de Carvalho (2001)
This text presents some of Donald Davidson's basic notions concerning language and interpretation, emphasizing his holistic theoiy of meaning, his criticism of the conceptual scheme/empirical contents duafism, and the role played by incommensurability in radical interpretation. The Davidsonian theory of meaning proposes a holistic approach withrespect to the notions of reference, meaning and truth. Witli this, Davidson allows the talk about extensionality and objectivit}' in the world without getting support fi-om the traditional theories of reference. On the basis of the thesis according to which there is no "third elemenf mediating between language and world, - be such a "clement" a "sensedatum", as required by the realists, or be it a "conventional meaning", as required by the anti-realists, - it now becomes possible to work the notion of incommensurability as a sort of temporally interrupted communication. Davidson discards the foundationalist use of tlie notion of reference in translating processes and considers only partial failures in translation.The appeal to the notion of incommensurability as a momentary break of communication helps to find out, for instance, to what extent a certain meaning in conventional language looses its use and why tliis happens. The whole approach involves a dmamic conception on language, of which the meanings var>' according to use.